2017
DOI: 10.5194/tc-11-1351-2017
|View full text |Cite
|
Sign up to set email alerts
|

Wind-driven snow conditions control the occurrence of contemporary marginal mountain permafrost in the Chic-Choc Mountains, south-eastern Canada: a case study from Mont Jacques-Cartier

Abstract: Abstract. We present data on the distribution and thermophysical properties of snow collected sporadically over 4 decades along with recent data of ground surface temperature from Mont Jacques-Cartier (1268 m a.s.l.), the highest summit in the Appalachians of south-eastern Canada. We demonstrate that the occurrence of contemporary permafrost is necessarily associated with a very thin and wind-packed winter snow cover which brings local azonal topo-climatic conditions on the dome-shaped summit. The aims of this… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Both and Grünberg et al (2020) found that snow depth and, most likely, snow structural differences, lead to pronounced differences in mean soil temperature, soil temperature variability and timing of snowmelt, across different vegetation types. Multiple field based studies have found that the thermal impacts of variations in snow thickness over natural gradients can explain more of the spatial variability in ground temperatures than key climate variables such as mean annual air temperature (Granberg 1988;Davesne et al 2017;Pelletier et al 2019;Davis et al 2020;Garibaldi et al 2021;Kropp et al 2021). Some modelling studies have shown that deeper snow thicknesses found particularly in tall vegetation may altogether prevent the formation of permafrost in regions that would otherwise be climatically suitable (Smith and Riseborough 2002;Tutton and Way 2021;Way and Lapalme 2021).…”
Section: ) Soil Temperaturesmentioning
confidence: 99%
“…Both and Grünberg et al (2020) found that snow depth and, most likely, snow structural differences, lead to pronounced differences in mean soil temperature, soil temperature variability and timing of snowmelt, across different vegetation types. Multiple field based studies have found that the thermal impacts of variations in snow thickness over natural gradients can explain more of the spatial variability in ground temperatures than key climate variables such as mean annual air temperature (Granberg 1988;Davesne et al 2017;Pelletier et al 2019;Davis et al 2020;Garibaldi et al 2021;Kropp et al 2021). Some modelling studies have shown that deeper snow thicknesses found particularly in tall vegetation may altogether prevent the formation of permafrost in regions that would otherwise be climatically suitable (Smith and Riseborough 2002;Tutton and Way 2021;Way and Lapalme 2021).…”
Section: ) Soil Temperaturesmentioning
confidence: 99%
“…The onset of a stable snowpack is known to be a critical factor for the soil surface thermal regime (Ling and Zhang, 2003), and hence for the temperature gradient into the snowpack. An early snow onset, as it occurred at WHI and RB in the fall of 2018, prevents rapid cooling of the soil because it is partially disconnected from atmospheric conditions (Ishikawa, 2003; Davesne and others, 2017). However, data from WHI show that the soil surface temperature cooled quite rapidly despite the presence of the snowpack (Figs 9a, c and Figs S3a, b).…”
Section: Discussionmentioning
confidence: 99%
“…Spatially and temporally dense monitoring of temperature -acquired at hundreds of locations distributed across several square kilometers-have primarily focused on air (Alcoforado and Andrade, 2006;Holden et al, 2016;Hubbart et al, 2005;Whiteman et al, 2000) and ground surface temperature (Davesne et al, 2017;Gisnås et al, 2014;Gubler et al, 2011;Lewkowicz et al, 2012). For example, dense air temperature measurements from 1600 self-recording temperature sensors, across a domain extending from the Boise Basin, Idaho, to southern British Columbia, have been used to evaluate downscaling of air temperature from long-term weather stationsusing covariates that have established physical links to surface air temperature (Holden et al, 2016).…”
Section: Introductionmentioning
confidence: 99%